2013
DOI: 10.1093/abbs/gmt044
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β peptide (1–42) aggregation induced by copper ions under acidic conditions

Abstract: It is well known that the aggregation of amyloid-b peptide (Ab) aggregates. The aggregation rate of Ab was increased with the elevation of temperature. These results were further confirmed by fluorescence spectroscopy and circular dichroism spectroscopy and it was found that the formation of b-sheet structure was inhibited by Cu 21 binding to Ab.The result was consistent with AFM observation and the fibrillation process was restrained. We believe that the local charge state in hydrophilic domain of Ab may pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 43 publications
(56 reference statements)
0
16
0
Order By: Relevance
“…Yoshiike et al reported that positively charged Aβ fibrils/profibrils are highly cytotoxic, and neutralization of the charges could reduce neuronal toxicity [8] . Moreover, covalent modification of the charged amino groups of Aβ peptides through glycation and acylation could significantly reduce cytotoxicity of Aβ species [8a] .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Yoshiike et al reported that positively charged Aβ fibrils/profibrils are highly cytotoxic, and neutralization of the charges could reduce neuronal toxicity [8] . Moreover, covalent modification of the charged amino groups of Aβ peptides through glycation and acylation could significantly reduce cytotoxicity of Aβ species [8a] .…”
mentioning
confidence: 99%
“…Yoshiike et al reported that positively charged Aβ fibrils/profibrils are highly cytotoxic, and neutralization of the charges could reduce neuronal toxicity [8] . Moreover, covalent modification of the charged amino groups of Aβ peptides through glycation and acylation could significantly reduce cytotoxicity of Aβ species [8a] . In addition, Yang et al showed that surface coating of Aβs with open-chain conjugates of polyether-thioflavin analogues could reduce the adhesion of Aβs towards Anti-Aβ IgG, and could ameliorate dendritic spine density and improve cognitive function in an AD mouse model [9] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed analysis has shown that Cu(II) hinders the formation of the β-sheet while still promoting the aggregation of the peptide 283 , and in addition AFM and EM have shown that Cu(II) has a similar effect on other amyloid peptides. When human islet amyloid polypeptide is incubated with Cu(II) fibrillisation is suppressed but the population of aggregates is smaller, and increased ROS over-production and mitochondrial dysfunction are noted 283 .…”
Section: Resultsmentioning
confidence: 99%
“…A--beta binds 691 copper with high affinity, and demonstrates enzyme--like activity, oxidizing 692 cholesterol and reducing O2 to H202 (47). Copper induces Abeta aggregation 693 amorphously, and inhibits Beta--sheet structure formation (48 (33). Alpha--synuclein resides in lipid rafts and binds to GM1, promoting 717 oligomer formation (33).…”
Section: Transmissible Spongiform Encephalopathymentioning
confidence: 99%